Finite Element Modelling Of Reinforced Concrete Beams With A Hybrid Combination Of Steel And Glass Polymer Reinforcement - Ahmad, Nur Ain; Salleh, Norhafizah (Recent Trends in Civil Engineering and Built Environment, 2022)
Finite Element Modelling of Hybrid Reinforced Concrete Beam (HRCB) with the combination of steel and GFRP reinforcement were constructing on Atena Engineering Software, referred to experimental data from previous testing investigation at laboratory, the result analysis proved the validation of HRCB between it, based on the result of load deflection graph of the finite element modeling in Atena Engineering Software and compared experimental data. The percentage of validation between experimental data and Atena Engineering Software for all types of RC beam which is for Control beam that are 2.1% for BS and 4.8% (BG) and for Hybrid beams that are 2.2% for BH-1, 2.7%  for BH-1, 2.9% for BH-3, 0.01% for BH-4, 1.7% for BH-5) and 0.7% for BH-6. During the analysis of finite element modeling, Crack pattern will be occurred and produced crack failure on the beam which is for BS was shear Flexural failure , BG was Shear failure, BH-1 was shear failure, BH-2 was Flexural failure, BH-3 was Shear Failure, BH-4 was flexural failur,BH-5 was Shear Failure and BH-6 was flexural failure. The analyses of properties effect between types Fiber reinforce Polymer (FRP) bars, which is Aramid (AFRP), Basalt (BFRP), Carbon (CFRP) and Glass (GFRP). The result of load deflection parametric shown CFRP has the highest flexural strength compares to others affected by the materials properties inside the CFRP bar.